EMI through virtual exchange at Bordeaux University - Alexandra Reynolds (University of Groningen Press, 2022)
The ongoing trend towards the internationalisation of universities in Europe places English as a Medium of Instruction (EMI) for education firmly on institutional agendas. This study carried out at Bordeaux University, France, explores EMI through Virtual Exchange (VE). The combination of both EMI and VE is presented here as a new area of study which we will refer to as EMI-VE. The report evaluates students' perceived linguistic progress and transdisciplinary learning competences through Erasmus VE (EVE). This multi-institutional EMI-VE context provides much needed international interaction lacking in home EMI models.